The Impact of Enforcement Baznas Toward Funds Collection Before and During Covid 19 Pandemic: Pengaruh Kinerja Badan Amil Zakat Nasional Terhadap Penghimpunan Dana Zakat Sebelum dan Selama Pandemi Covid -19 - Abdul Jalil; Mochammad Syahfril Moharom; Ermawati; Irham Pakkawaru; Ma’rifah Nurmala (Journal of Islamic Economics Perspectives, 2023)
Indonesia is the largest Muslim-majority population in the world, makes this country has enermous potential toward zakat funds. Palu city has a large zakat potential in fact, the zakat funds collected succeeding to be expected. Moreover, Indonesia and other countries are experiencing a fairly dangerous Covid-19 outbreak. However, when the world economy deteriorated due to the pandemic, a funds at Palu showed high increasing before Pandemic. The common problem is whether is there a difference between the enforcement of BAZNAS in collecting zakat funds before and during the Covid-19 pandemic. The method was a quantitative of comparative analysis. The sample used a probability sampling technique and obtained 32 respondents and questionnaires distribution. This study used the analysis method of Paired Sample T Test Differences by fulfilling Classical Assumption. Based on the results of Paired Sample T Test, there is no difference between the enforcement of the Palu City BAZNAS before and during the Pandemic. The collection of zakat funds cannot be separated from the role of the National Amil Zakat Agency itself so socialization and approaches must be maximized build cooperation with agencies in order the collection of zakat funds in the city would run as expected.